Answer:
bbbbbbbbbbbbbbbbbbbbbbbbbb
Step-by-step explanation:
Answer: x = 1
3x + 4 = 7
subtract 4 from both sides
3x = 3
x = 3/3 = 1
Answer:
no >:)
Step-by-step explanation:
Answer:
x=3
Step-by-step explanation:
lets take x as the number
so
6(x-3)=x-3
since it says "6 times" we know that we will have to multiply the difference by 6 and it says the difference of a number and 3 is equal to 3 less than the number so we know that we are subtracting 3 from x
6x-18=x-3
6x-x=18-3
5x=15
x=3
Answer:
<em>when </em><em>x </em><em>=</em><em> </em><em>5</em><em> </em>
<em>then </em><em> </em><em>the </em><em>value </em><em>of</em><em>. </em><em>(</em><em>3</em><em>x</em><em>+</em><em>2</em><em>)</em>
<em>(</em><em>3</em><em>*</em><em>5</em><em>)</em><em> </em><em>+</em><em> </em><em>2</em>
<em> </em><em> </em>
<em>1</em><em>5</em><em> </em><em>+</em><em> </em><em>2</em>
<em>=</em><em>. </em><em>1</em><em>7</em>
<em>her </em><em>mistake </em><em>was </em><em>that </em><em>she </em><em>doesn't</em><em> </em><em>multiplied</em><em> </em><em>5</em><em> </em><em>and </em><em>3</em><em> </em><em> </em>